Use of Smart Boxes to Increase Learning Interest in Early Childhood (Journal of Didactic Studies, 2024)
This study aims to determine the use of smart box educational toys in increasing the learning interest of early childhood at RA Persis 237 An-Nur and also to identify the obstacles and solutions in using smart box educational toys in increasing the learning interest of early childhood. The method used in this study is a qualitative research method with a case study approach. Data collection techniques and instruments used observation, interviews, documentation studies, and triangulation. The results of the study show that: 1) The use of smart boxes can increase children's interest in learning, as seen from increased active participation, feelings of joy, and children's attention or enthusiasm in participating in learning activities. 2) However, there are still obstacles that must be overcome, namely the limitations of smart box toys, the need for more time, the lack of understanding among teachers, and teacher supervision during activities. However, the above obstacles can be overcome with solutions, including a learning environment that supports children's creativity, children's enthusiasm in participating in activities, collaboration between the school and parents, and teachers' creativity and understanding in using smart box toys.